1991
DOI: 10.1093/ajcn/53.4.1068s
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of tocopherol and tocotrienol for the chemoprevention of chemically induced rat mammary tumors

Abstract: Two forms of vitamin E, tocopherol and tocotrienol, were tested for chemopreventive activity in two chemically induced rat mammary-tumor models. When mammary tumors were induced by 7,12-dimethylbenz(a)anthracene (DMBA, 50 mg/kg), only the tocotrienol group had a statistically significant increase in tumor latency. There was no effect of either compound on tumor multiplicity. When tumors were induced by N-nitrosomethylurea (NMU, 30 mg/kg), neither analogue of vitamin E modified latency, whereas tocotrienol incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(32 citation statements)
references
References 1 publication
0
32
0
Order By: Relevance
“…T3 has been shown to mediate its activity against a variety of chronic diseases, including cardiovascular diseases, neurologic diseases, diabetes, and cancer (9)(10)(11)(12)(13)(14). T3s have shown anticancer activity against cancers such as colon, breast, liver, lung, kidney, prostate, skin, and other cancers both in vitro (15)(16)(17)(18)(19)(20) and in vivo (21)(22)(23)(24)(25). T3 has the potency to induce apoptosis in a variety of cancer cell types (types 1-5).…”
Section: Introductionmentioning
confidence: 99%
“…T3 has been shown to mediate its activity against a variety of chronic diseases, including cardiovascular diseases, neurologic diseases, diabetes, and cancer (9)(10)(11)(12)(13)(14). T3s have shown anticancer activity against cancers such as colon, breast, liver, lung, kidney, prostate, skin, and other cancers both in vitro (15)(16)(17)(18)(19)(20) and in vivo (21)(22)(23)(24)(25). T3 has the potency to induce apoptosis in a variety of cancer cell types (types 1-5).…”
Section: Introductionmentioning
confidence: 99%
“…Tocotrienols from palm oil have been shown to inhibit proliferation and growth of various cancer cells including the breast, prostate and colon cancer cells both in vitro and in vivo (Nesaretnam et al 1992(Nesaretnam et al , 1995(Nesaretnam et al , 1998(Nesaretnam et al , 2004Guthrie et al 1997;Agarwal et al 2004;Srivastava and Gupta 2006;Gould et al 1991).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, g-tocotrienol has been reported to suppress the proliferation of a wide variety of tumor cells (15), including gastric (16)(17)(18)(19), hepatocellular carcinoma (20), melanoma (21), breast (22), colorectal (23), and prostate (24). In vivo mice studies have shown that g-tocotrienol can suppress the growth of breast tumor (25), prostate (26), lung cancer and melanoma (27) and also inhibit the growth of liver and pancreatic cancer either alone or in combination with chemotherapeutic drugs and radiation (28,29). How g-tocotrienol mediates its anticancer effects is not completely understood, but the roles of various signaling cascades/kinases/transcription factors such as mitogen-activated protein kinases (17), phosphoinositide 3-kinase (PI3K)/Akt (30), NF-kB (13), STAT3 (20), telomerase (31), PPAR-g (32), hypoxiainducible factor-1a (33), b-catenin (23), EGF (24), and inhibitor of differentiation family proteins (34) have been implicated.…”
Section: Introductionmentioning
confidence: 99%